Vitamin D3 protects against Aβ peptide cytotoxicity in differentiated human neuroblastoma SH- SY5Y cells: A role for S1P1/p38MAPK/ATF4 axis. (April 2017) - Pierucci, Federica; Garcia-Gil, Mercedes; Frati, Alessia; Bini, Francesca; Martinesi, Maria; Vannini, Eleonora; Mainardi, Marco; Luzzati, Federico; Peretto, Paolo; Caleo, Matteo; Meacci, Elisabetta
Abstract: Besides its classical function of bone metabolism regulation, 1alpha, 25-dihydroxyvitamin D3 (1, 25(OH)2 D3 ), acts on a variety of tissues including the nervous system, where the hormone plays an important role as neuroprotective, antiproliferating and differentiating agent. Sphingolipids are bioactive lipids that play critical and complex roles in regulating cell fate. In the present paper we have investigated whether sphingolipids are involved in the protective action of 1, 25(OH)2 D3. We have found that 1, 25(OH)2 D3 prevents amyloid-β peptide (Aβ(1−42)) cytotoxicity both in differentiated SH-SY5Y human neuroblastoma cells and in vivo . In differentiated SH-SY5Y cells, Aβ(1−42) strongly reduces the sphingosine-1-phosphate (S1P)/ceramide (Cer) ratio while 1, 25(OH)2 D3 partially reverts this effect. 1, 25(OH)2 D3 reverts also the Aβ(1−42)-induced reduction of sphingosine kinase activity. We have also studied the crosstalk between 1, 25(OH)2 D3 and S1P signaling pathways downstream to the activation of S1P receptor subtype S1P1. Notably, we found that 1, 25(OH)2 D3 prevents the reduction of S1P1 expression promoted by Aβ(1−42) and thereby it modulates the downstream signaling leading to ER stress damage (p38MAPK/ATF4). Similar effects were observed by using ZK191784. In addition, chronic treatment with 1, 25(OH)2 D3 protects from aggregated Aβ(1−42)-induced damage in the CA1 region of the rat hippocampus and promotes cell proliferation in the hippocampal dentate gyrus of adult mice. In conclusion, these results represent the first evidence of the role of 1, 25(OH)2 D3 and its structural analogue ZK191784 in counteracting the Aβ(1−42) peptide-induced toxicity through the modulation of S1P/S1P1/p38MAPK/ATF4 pathway in differentiated SH-SY5Y cells. Highlights: 1, 25(OH)2 D3 increases the level of the pro-survival S1P while decreases that of pro-apoptotic ceramide in SH-SY5Y cells. The neuroprotective effect of 1, 25(OH)2 D3 against the β-amyloid-induced toxicity involves the receptor subtype S1P1 signaling. Downstream signaling of S1P1 in 1, 25(OH)2 D3 -induced neuroprotection involves p38MAPK/ERK/ATF4 axis. 1, 25(OH)2 D3 -analogue ZK191784 mimics hormone action in neuroprotection against β-amyloid- induced toxicity.